SUPPLY CHAIN ​​ANALYSIS OF BLUE SWIMMING CRAB (Portunus pelagicus) KARAWANG REGENCY (CASE STUDY: CILAMAYA WETAN AND TIRTAJAYA DISTRICTS): ANALISIS RANTAI PASOK RAJUNGAN (Portunus pelagicus) KABUPATEN KARAWANG(STUDI KASUS: KECAMATAN CILAMAYA WETAN DAN TIRTAJAYA) - Ratih Purnama Sari; Dendi Haris; Rakhma Fitria Larasati; Muhamad Riyono Edi Prayitno; Robet Perangin-angin; Suharyanto Suharyanto; R. Mohamad Adha Akbar (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2026)
The blue swimming crab is a leading commodity in Karawang Regency in terms of economic value. It is marketed locally and internationally. Blue swimming crabs are sold to consumers both alive and processed, so a supply chain process is needed that can meet consumer demand quickly and maintain excellent quality. This study aims to analyze the management, structure, and costs of the blue swimming crab supply chain and evaluate its external performance using the Supply Chain Operations Reference (SCOR) method, which is considered a systematic approach for measuring supply chain performance. This study was conducted in Tirtajaya District, Cilamaya Wetan District, and at a blue swimming crab processing company in Cirebon. The results of this study include an explanation of the supply chain targets, supply chain structures, types of costs incurred by fishermen, traders, collectors, and suppliers, as well as the value of the external performance of the supply chain. The research subjects consisted of fishermen, traders, and collectors. The structure of the blue swimming crab supply chain in Karawang Regency had two different flows or chain networks from fishermen to suppliers. The costs generally incurred are operational costs, including diesel fuel, supplies, fishing gear, bait (if using traps), and transportation. External performance measurements of the blue swimming crab supply chain in Karawang Regency consistently yield superior results across all indicators. However, the order fulfillment indicator yielded parity due to the lean season.